Domestic Violence Experienced by Lily Bloom in Coleen Hoover’s It Ends With Us - Salsabila, Izza Hanum (Universitas Negeri Surabaya, 2024)
This research examines the dynamics of domestic violence (KDRT) and Lily Bloom's escape from a violent relationship in the novel It Ends With Us by Colleen Hoover. Based on Lenore Walker's cycle of violence theory, this research analyzes how Lily experiences repeated violence from her husband, Ryle Kincaid. Research findings show that the domestic violence experienced by Lily follows a cyclical pattern consisting of three phases; (1) Tension-Building, characterized by increasing tension in Lily and Ryle's relationship because small fights, disagreements and frustration become the initial trigger. (2) Acute Violence Phase, which is the peak of the cycle of violence, where Ryle commits acts of physical violence against Lily. (3) Reconciliation Phase which shows Ryle's regret and apology.